2017
DOI: 10.1371/journal.pntd.0005303
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Carbon Substrate Profiling of Mycobacterium ulcerans Suggests Potential Environmental Reservoirs

Abstract: BackgroundMycobacterium ulcerans is a close derivative of Mycobacterium marinum and the agent of Buruli ulcer in some tropical countries. Epidemiological and environmental studies pointed towards stagnant water ecosystems as potential sources of M. ulcerans, yet the ultimate reservoirs remain elusive. We hypothesized that carbon substrate determination may help elucidating the spectrum of potential reservoirs.Methodology/Principal findingsIn a first step, high-throughput phenotype microarray Biolog was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 40 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…The degradation products serve as an important nutrient source for bacteria in the nature 51 . M. ulcerans may obtain energy and carbon from the degradation of plant saccharides which were demonstrated to stimulate M. ulcerans growth in vitro 14 , 53 . It was recently shown that chitin promoted growth of M. ulcerans 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The degradation products serve as an important nutrient source for bacteria in the nature 51 . M. ulcerans may obtain energy and carbon from the degradation of plant saccharides which were demonstrated to stimulate M. ulcerans growth in vitro 14 , 53 . It was recently shown that chitin promoted growth of M. ulcerans 43 .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent high-throughput carbon substrate profile of M. ulcerans in our laboratory, we found a significant association between the M. ulcerans core biologome and bacteria, fungi, algae, and mollusks. We concluded that environmental M. ulcerans research should increase its focus on fungi, algae, and mollusks, because they contain the nutrients necessary for the survival of M. ulcerans (211).…”
Section: Areas Of Uncertainties and Perspectivesmentioning
confidence: 99%
“…Buruli ulcer has also been encountered in aquatic invertebrates, mosquitoes (13, 16, 19, 91, 107, 113, 139, 141, 149, 150, 152-154, 156, 193), crayfish (108), amoeba, mollusks, crustaceans, annelida (29,40,141,153), aerosols, water, biofilm, moss, detritus, feces, plants, and soil (13,29,39,63,93,106,107,112,113,(144)(145)(146)(147)210). The hypothesis most advanced to aggregate data issuing from the investigations on the environment is that M. ulcerans may be part of a food chain (211,212).…”
Section: Buruli Ulcer In Animalsmentioning
confidence: 99%
“…Differential metabolomics analysis is carried out for detection of eventual interaction of compound 1 with cellular subsystems. By using Phenotype MicroArray-based approach 16 , 17 , the differential analysis of B. cereus ATCC 14579 metabolism shows selective inhibition to several carbon sources. The associated metabolic pathways are identified according to the KEGG (Kyoto Encyclopedia of Genes and Genomes) database and hierarchical mapped (Supplementary Fig 9 ).…”
Section: Resultsmentioning
confidence: 99%